Mallory bodies in alcoholic and non-alcoholic liver disease contain a common antigenic determinant. Issue 5 (May 1981) - Fleming, K A; Morton, J A; Barbatis, C; Burns, J; Canning, S; McGee, J O
Abstract : An immunohistochemical technique is described for the detection of Mallory bodies (MBs) in paraffin sections of liver tissue. This is based on proteolytic digestion of sections before exposure to an antiserum which recognises a unique antigenic determinant in MBs. With the use of this procedure it has been shown in alcoholic liver disease, primary biliary cirrhosis. Indian childhood cirrhosis, Wilson's disease, diabetes mellitus, and hepatocellular cancer that the MBs found in these disorders contain this unique antigenic determinant. It is postulated, therefore, that the mechanism of formation of MBs is similar in liver diseases of diverse aetiology. In addition, it has been demonstrated that the immunohistochemical procedure is more sensitive than routine staining; MBs were detected in five out of 12 fatty livers by immunohistochemical and only in one by H and E staining. As MBs in fatty livers were not associated with polymorph filtration or fibrogenesis it is argued that MB formation is not an absolute prerequisite for the progression of acute to chronic liver disease.